Focus of the IPCC Assessment Reports Has Shifted to Lower Temperatures. Issue 5 (11th May 2022) - Jehn, Florian U.; Kemp, Luke; Ilin, Ekaterina; Funk, Christoph; Wang, Jason R.; Breuer, Lutz
Abstract: We focus on how different global temperature increases represented in IPCC reports have shifted over time. While the first four assessment reports had a roughly equal focus on temperatures above and below 2°C, the more recent fifth and sixth assessment reports have a considerably stronger focus on warming below 2°C. This is concerning as warming above 2°C is more likely given current emissions trajectories and is more influential on climate risk assessments. Key Points: The focus of the IPCC has shifted to lower temperatures, beginning with assessment report 5 Only 14 % of the temperature mentions in assessment report 6 are above 2°C, in contrast to our current trajectory in which temperatures above 2°C seem likely